Custos da doença atribuíveis à hipercolesterolémia em Portugal - Gouveia, Miguel (2004)
Cardiovascular diseases are the main cause of death in Portugal, in developed countries and, indeed, worldwide. Hypercholesterolemia is a major risk factor for these diseases, including ischemic heart disease, cerebrovascular disease, and peripheral vascular disease. This paper reports the results of a study of the cost of illness associated with hypercholesterolemia and the costs directly attributable to hypercholesterolemia in Portugal, estimated from data for the year 2000. The results indicate that the cost of the health care provided to deal with illnesses associated with hypercholesterolemia was Euros 735.9 million (direct costs) and the costs of lost production due to disability of patients of working age was Euros 74.82 million (indirect costs). The costs attributable to hypercholesterolemia, those that would be avoided if hypercholesterolemia were completely eliminated, amount to Euros 358.84 million in direct costs and Euros 28.31 million in indirect costs. These results confirm that hypercholesterolemia is a source of major health costs. This means that hypercholesterolemia deserves special attention from those who formulate health policy and should be given priority in implementing such policies.